Analysis of ground water distribution using robust constrain inversion determination geoelectric data of wenner configuration type in Bukit Lantiak, Padang Selatan District - Silvia Dona Sari (PILLAR OF PHYSICS, 2014)
The aimed of this research are to determine the distribution, depth, and types of groundwater aquifers in Bukit Lantiak  Padang Selatan area. Distribution of groundwater in Bukit Lantiak are important to know to anticipated landslide cause increase in soil water content in the slope. This research used resistivity geoelectric method of Wenner configuration. Data of this research taken four tracks using ARES (Automatic Resistivity). Interpretation data was done by with Robust Constraint inversion. The results of this research showed that distribution of soil water on Tracks 1, 3, and 4 tend to lead from the Northeast to the Southwest. Distribution of groundwater in track 2 leads from West to East. Into the ground water ranged from 5.76 to 30.2 m were obtained. Type aquifer is an aquifer that is found free and depressed. Free aquifers that can trigger landslides from on track 1